Towards a CAD-based automatic procedure for patient specific cutting guides to assist sternal osteotomies in pectus arcuatum surgical correction. Issue 1 (3rd January 2018) - Carfagni, Monica; Facchini, Flavio; Furferi, Rocco; Ghionzoli, Marco; Governi, Lapo; Messineo, Antonio; Uccheddu, Francesca; Volpe, Yary
Graphical abstract: Abstract: Pectus Arcuatum, a rare congenital chest wall deformity, is characterized by the protrusion and early ossification of sternal angle thus configuring as a mixed form of excavatum and carinatum features. Surgical correction of pectus arcuatum always includes one or more horizontal sternal osteotomies, consisting in performing a V-shaped horizontal cutting of the sternum (resection prism) by means of an oscillating power saw. The angle between the saw and the sternal body in the V-shaped cut is determined according to the peculiarity of the specific sternal arch. The choice of the right angle, decided by the surgeon on the basis of her/his experience, is crucial for a successful intervention. The availability of a patient-specific surgical guide conveying the correct cutting angles can considerably improve the chances of success and, at the same time, reduce the intervention time. The present paper aims to propose a new CAD-based approach to design and produce custom-made surgical guides, manufactured by using additive manufacturing techniques, to assist the sternal osteotomy. Starting from CT images, the procedure allows to determine correct resection prism and to shape the surgical guide accordingly taking into account additive manufacturing capabilities. Virtually tested against three case studies the procedure demonstrated its effectiveness.